2022
DOI: 10.1108/ijppm-04-2021-0232
|View full text |Cite
|
Sign up to set email alerts
|

Employer attractiveness, employee engagement and employee performance

Abstract: PurposeThis study examines the effects of employer attractiveness (EA) on employee engagement (EE) and employee performance (EP).Design/methodology/approachMixed method. The analytical technique is the Partial Least Squares Structural Equation Modeling through survey questionnaires collected from 937 respondents as employees from 37 enterprises in Vietnam.FindingsEA has a positive impact on EE and EP factors. However, EE has no statistically significant impact on EP.Practical implicationsThis study helps manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 91 publications
0
2
1
Order By: Relevance
“…Empirical studies (Al-dalahmeh et al, 2018), (Lewiuci, P. & Mustamu, R., 2017) and (Maryati & Astuti, 2022) have demonstrated that employee engagement significantly affected employee performance. Employee engagement, contrary to studies (Rahmadalena & Asmanita, 2020) and (Nguyen & Nguyen, 2022), did not affect productive employee behavior.…”
Section: Introductioncontrasting
confidence: 92%
“…Empirical studies (Al-dalahmeh et al, 2018), (Lewiuci, P. & Mustamu, R., 2017) and (Maryati & Astuti, 2022) have demonstrated that employee engagement significantly affected employee performance. Employee engagement, contrary to studies (Rahmadalena & Asmanita, 2020) and (Nguyen & Nguyen, 2022), did not affect productive employee behavior.…”
Section: Introductioncontrasting
confidence: 92%
“…Engagement offers employees the opportunity to invest themselves in their work and fosters a sense of self-efficacy. Research exploring the ramifications of employee engagement suggests that it can yield positive outcomes in terms of employee well-being and cultivate favourable attitudes towards work and the organization (Nguyen & Nguyen, 2022). Employee engagement, in essence, denotes the extent to which individuals exhibit identification with their work, actively participate therein, and ascribe importance to their performance as a reflection of their self-worth (Yandi & Havidz, 2022).…”
Section: Employee Engagement and Employee Performancesmentioning
confidence: 99%
“…However, researchers are interested in studying employee attraction from the perspective of current employees. Nguyen et al (2021) [26] also experimented with the impact of employer attractiveness on current employees. Dassler et al (2022) [19] grouped the literature on employer attractiveness into two phases -'Laying the ground (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)' where potential employees are focused on, and 'Rise of employee focus (from 2010 onwards)' where perceptions of present employees are studied.…”
Section: Introductionmentioning
confidence: 99%